World tax reform : a progress report - Pechman, Joseph A.; Brookings Institution (Washington, D.C. : Brookings Institution, 1988)
A report of a conference held in Washington, D.C., on November 12-13, 1987, sponsored by the Brookings Institution.
"Report of a conference held in Washington, D.C., on November 12-13, 1987, sponsored by the Brookings Institution."
Includes bibliographical references.
oif 28/01/2019
Loans
Keywords: Taxation; Tax reform